CALCULATION OF NEUTRON FLUX DISTRIBUTION AT PIERCING BEAM PORTS OF PLATE TYPE RESEARCH REACTOR BANDUNG - Epung Saepul Bahrum; Prasetyo Basuki; Alan Maulana; Jupiter Sitorus Pane (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2020)
Based on a strategic plan of TRIGA 2000 Bandung’s future operation, BATAN has already decided to implement an option to convert the fuel elements core of TRIGA 2000 from using the cylindrical type of elements produced by General Atomic to MTR plate type of fuel elements produced by local fuel element manufacture.  The core design calculation has proved that the core configurations of 5 x 5 matrix using local plate type fuel elements met the requirement of core neutronics design. In addition to the current core configuration, further study must be added to consider the use of beam ports as utilization facilities in the design.  The neutron flux distribution at piercing beam port has been calculated based monte carlo algorithm using TRIGA MCNP and MCNP software. The calculation result showed that at piercing beam port surface neutron flux distribution is not quite symmetric. The highest neutron flux at piercing beam port is , where as the flux of neutron thermal energy group is . These results are considerably appropriate for such core configuration and as a result, they can be used as a basic data for designing Plate Type Research Reactor Bandung, especially for neutron diffraction experiment